Pengaruh Laba Bersih dan Arus Kas Operasional terhadap Kebijakan Dividen Pada Perusahaan yang Terdaftar Di BEI Periode 2007 – 2011 - Nurrochim, Slamet; Indarti, Iin (STIE Widya Manggala, 2013)
This study aimed to analyze the influence of Net earning and Operating Cash flow to the Dividend Policy of companies in Indonesia Stock Exchange in 2007-2011. The samples in this study were 27 companies in Indonesia Stock Exchange in 2007-2011. And analyzed by multiple linear regresion. The result showed that Net Earnings had no significant influence on Dividend Policy, meanwhile Operating Cash Flow had a negative influence on Dividen Policy.